Corruption abuse of humanitarian and free aid in the context of armed conflicts: a comparative legal study - O. S. Bondarenko (Law and Safety)
The article is devoted to the analysis of an extremely important topic under martial law, which is the characteristics of certain corrupt practices in relation to free and humanitarian aid in foreign countries and Ukraine, with the aim of finding optimal ways to combat corruption in the sphere of rational and effective use of free and humanitarian aid during armed conflicts.